Technical note: On HALOE stratospheric water vapor variations and trends at Boulder, Colorado - E. Remsberg (Atmospheric Chemistry and Physics, 2023)
This study compares time series of stratospheric water vapor (SWV) data at 30 and 50 hPa from 1993 to 2005, based on sets of Halogen Occultation Experiment (HALOE) profiles above the region of Boulder, CO (40∘ N, 255∘ E), and on local frost-point hygrometer (FPH) measurements. Their differing trends herein agree with most of the previously published findings. FPH trends are presumed to be accurate within their data uncertainties, and there are no known measurement biases affecting the HALOE trends. However, the seasonal sampling from HALOE is deficient at 40∘ N from 2001 to 2005, especially during late winter and springtime, when HALOE SWV time series at 55∘ N clearly show a springtime maximum. This study finds that the SWV trends from HALOE and FPH measurements nearly agree within uncertainties at 30 hPa for the more limited time span of 1993 to 2002. Yet, HALOE SWV at 50 hPa has significant and perhaps uncertain corrections for interfering aerosols from 1992 to 1994. Northern Hemisphere time series and daily SWV plots near 30 hPa from the Limb Infrared Monitor of the Stratosphere (LIMS) experiment indicate that there is transport of filaments of high SWV from polar to middle latitudes during dynamically active winter and springtime periods. Although FPH measurements sense SWV variations at all scales, the HALOE time series do not resolve smaller-scale structures because its time series data are based on an average of four or more occultations within a finite latitude–longitude sector. It is concluded that the variations and trends of HALOE SWV are reasonable at 40∘ N and 30 hPa from 1993 to 2002 and in accord with the spatial scales of its measurements and sampling frequencies.